Penggunaan Pengaruh Media Video Pembelajaran Terhadap Hasil Belajar Siswa SMA Kelas X - Manein, Adelia Desterina; Marianus; Silangen, Patricia Mardiana (Charm Sains: Jurnal Pendidikan Fisika, 2022)
This study aims to determine the effect of using instructional video media on the learning outcomes of high school students in class X on energy materials. This research was conducted at SMA Negeri 1 Beo. The research design used a pretest posttest control group design, with the research sample being the experimental class and the control class. The experimental class was treated with learning using video while the control class did not use video. The instrument used in the study was a multiple-choice test. Based on descriptive statistical analysis, the average value of the control class was 6.48 and the average value of the experimental class was 7.86. Based on the results of the independent simple t-test, the value of -ttable > tcount then Ha is accepted and H0 is rejected. So it can be concluded that there is an effect of using instructional video media on student learning outcomes. The use of learning video media has a good influence on student learning outcomes.